Evaluation of prolific hybrids maize performance on different population densities and nitrogen level. Issue 1 (April 2020) - Efendi, R; Baharuddin,; Herawati,; Andayani, N N; Kalqutny, S H; Azrai, M
Abstract: Prolificacy in maize is an adaptability character, with influence on production capacity and production stability. Prolificacy is the maize natural property to develop more ears on the same plant. Prolificacy maize can produce more than one ear per plant so it can increase the production per unit area of land. In addition, prolific maize is able to utilize the growth factors more efficiently and has higher yield stability compared to non-prolific maize. Prolific hybrid maize is also reported to be more tolerant to low humidity during the pollination and kernel filling phases. This study aims to determine the prolific percentage and yield of maize hybrid tested at different levels of population density and nitrogen fertilization. The study was conducted in September-December 2017 in Gowa using two candidates varieties of hybrid maize and NASA 29 and Bisi 2 variety as comparisons. The experiments were arranged in a split-plot design with three replications. The main plot is the spacing, ie. double spacing (50+100 cm) x 25 cm (Population of 53, 333 plants/ha) and (50+110 cm) x 20 cm (Population of 62, 500 plants/ha) and (50 + 100 cm) x 20 cm (Population of 66, 666 plants/ha). The subplots were the level of N fertilizer (150 and 225) kg N/ha), The sub-sub plot was the prolific hybrid genotypes (candidate for the multilocation test) and two check varieties of Bisi 2 and NASA 29. The result indicated that Bisi-2 variety has a high prolific percentage of 51.30%. 2. The Nasa-29 variety has the highest total kernel yield production of 11.5 t/ha. 3. Significant increase in yield per unit area can be achieved by assembling varieties that have a high percentage of prolific and average kernel weight per prolific plant ≥50% compared to the single-eared plants.